Evaluation of antimicrobial effect of lemon grass essential oil on biofilm forming pathogens in broth medium and on stainless steel chip: LMO Effect on Biofilm on SS chip - Rajuji, Jamunkar Shivani; Mishra, Santosh Kumar; Singh, Pranav Kumar; Sangwan, Vikas (Indian Journal of Dairy Science, 2024)
The objective of this study was to check the effect of lemongrass essential oil (LMO) on biofilm-forming selected pathogens in broth medium and on stainless steel chip. The antimicrobial effect of lemongrass essential oil  by well agar assay showed all four pathogenic strains were susceptible to LMO. 0.9% MIC was observed in strain B. cereus ATCC 10876 and it was 0.8% for both S. aureus ATCC 700698 and Proteus mirabilis ATCC 12453 strains. E. coli ATCC 10536 was found to be the species bearing the least MIC (0.6%). Time kill analysis with all four planktonic pathogens in broth medium by using 0.8% lemongrass essential oil (selected based on MIC) was checked at their stationary growth phase. E. coli was found most sensitive to LMO treatment and gave complete reduction within 20 min contact time,  while S. aureus gave 71% inhibition, Proteus mirabilis gave 53% inhibition after 80 min of treatment with LMO. Bacillus cereus was the most resistant among all against LMO and gave only 27% inhibition after 80 min of treatment. However, all the pathogens were inhibited completely after 24 h treatment with 0.8% LMO. On stainless steel chip against biofilm of S. aureus and E. coli, LMO (0.8%) treatment gave complete reduction within 24 h. This study demonstrated that LMO could be a reliable foodborne pathogen biofilm disrupter.